STRATEGI GURU DALAM MENGEMBANGKAN KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN DI TK BARUNAWATI PONTIANAK - Dimitri, Ranti Utari; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to describe the teacher’s strategy in developing interpersonal intelligence of aged 5-6 years at the Barunawati Kindergarten Pontianak. The method use isn this research is descriptive method with a qualitative research approach. Data subjects in this research are 2 teacher’s and 12 childern of group B2 with age 5-6 years in Barunawati Kindergarten Pontianak. The techniques used in this research were observation, interview, and documentation using data collection tools like is observation guidelines, interview guides, and documentation picture. The results of data analysis show that the strategies used by teacher’s in developing interpersonal intelligence in children aged 5-6 years in the aspects of cooperation, empathy, and social interaction are by educating, give a figures for children, teaching, stimulating, directing children and motivating children. The strategy is carried out by the teacher to children have a good interpersonal intelligence, especially in ascapts of cooperation, empathy, and social interaction.Keyword : Childern 5-6 Years Old, Interpersonal Intelligence, Teacher Strategy.